A case study of an English as a foreign language writing learner-TEFL program portfolio. - Ramos Medina, María Paola (2012)
This thesis describes two aspects of teaching English as a foreign language that are essential to be considered by any EFL teacher. The first is a student’s writing case study developed with the purpose of helping a pre-intermediate English language learner reinforce and acquire some writing strategies necessary for his future studies. The second component of this study is a TESOL/NCATE standard- based position paper elaborated with the purpose of contemplating all the requirements a well-qualified English teacher should have. Using evidence from the work done throughout the TEFL master’s program the researcher was able to self-evaluate her work as an EFL teacher and determine some aspects that need to be addressed to be a more competent teacher.